Reststrahlen spectroscopy of MgAl₂O₄ spinel - Boguslavska, N.N.; Venger, E.F.; Vernidub, N.M.; Pasechnik, Yu.A.; Shportko, K.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Using IR reflectance spectroscopy and surface polariton spectroscopy in the reststrahlen region, we investigated Czochralski-grown MgAl₂O₄ spinel. The computer analysis of variance made for spectra enabled us to get a mathematical model for reflection spectra of spinel. In our calculations we used consistent data for optical parameters (zero- and high-frequency permittivities, transverse optical phonon frequencies and corresponding damping coefficients) of spinel single crystals that have been obtained from comparison between the measured and calculated spectra. These data were used when studying attenuated total reflection spectra and dispersion curves for surface polaritons in MgAl₂O₄ spinel.